PENDEKATAN SISTEM INFORMASI GEOGRAFIS (SIG) DALAM PENENTUAN ZONA KERENTANAN TANAH: STUDI KASUS BERAMBAI, SEMPAJA UTARA, KOTA SAMARINDA - Reta Andila Ayuningrum; Hamriani Ryka; Efrina Chandra Agusti Putri; Jamaluddin . (Sekolah Tinggi Teknologi MIGAS, 2026)
This study aims to identify the geomorphological characteristics, drainage patterns, and landslide susceptibility levels in the Berambai area and its surroundings, North Samarinda District. The research method integrates analyses of morphometric data, lithology, and geological structures. The results indicate that the study area is a single structural origin landform, divided into three landform units: undulating/sloping (s1), hilly-undulating (s2), and sharply dissected hilly/steep (S3). genetically, this region is influenced by syncline structures and a right lag slip fault, which control the development of dendritic drainage patterns in the Northwest and East, and subdendritic patterns in the Central to Southern parts. Landslide susceptibility analysis reveals a dominance of the Moderate Susceptibility Zone (60.3%), covering residential areas, followed by the high susceptibility zone (31.3%) on steep slopes with open land, and the low susceptibility zone (8.4%) in densely vegetated flatlands. The correlation between steep slopes, geological structural control, and intensive land use is the primary factor driving the high risk of ground movement in the study location